Innovative Psychology Based Human Resource Management for Teachers in Vocational Schools - Zuyina Fadhilatul Mahmudah; Muhammad Ghafar (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Teacher burnout, reduced motivation, and declining professional commitment are persistent challenges in Indonesian vocational schools, particularly as the demands of industry-linked curricula and digital learning environments intensify. Conventional human resource management (HRM) approaches in schools focus predominantly on administrative and compliance functions, leaving the psychological dimensions of teacher work largely unaddressed. This qualitative phenomenological study investigates how an innovative psychology-based HRM model was designed, implemented, and experienced by teaching staff at a government-affiliated vocational school (SMK Pemkab Ponorogo). Data were collected through participant observation of three professional development workshop sessions, semi-structured individual interviews with twelve informants (the school principal, vice-principal, two HR administrators, four classroom teachers, and four vocational subject teachers), and document analysis of training materials, evaluation records, and institutional work plans. Data were analysed through the interactive model of Miles, Huberman, and Saldaña (2014) and triangulated across sources and methods. Findings indicate that the programme integrates three psychological frameworks Self-Efficacy Theory (Bandura, 1997), Psychological Well-Being (Ryff, 1989), and Self-Determination Theory (Deci, Olafsen, & Ryan, 2017) into a coherent, needs-responsive HRM cycle that encompasses recruitment aligned with teacher competency and interest profiles, psychology-informed training design, well-being support provisions, and career development pathways. Participants reported positive shifts in professional self-confidence, stress management capacity, and intrinsic motivation. These findings suggest that psychology-based HRM, when grounded in validated theoretical frameworks rather than generic professional development, offers a promising approach to sustaining teacher quality in vocational education contexts